1988
DOI: 10.1515/znc-1988-3-420
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Conversion and Degradation of Sex Pheromones in Antennae of the Male Silkworm Moth Antheraea polyphemus

Abstract: In living antennae of the male silkworm moth Antheraea polyphemus the pheromone compounds [6,7-3H]-6,11-hexadecadienyl acetate and [12,13-3H]-10,12-hexadecadienol are enzymatically converted to their corresponding fatty alcohols, aldehydes, acids and long-chained fatty acid esters. In antennae of freshly hatched moths the 3H-labeled pheromones are degraded at high rates to volatile polar metabolites. The half-life of the pheromone acetate is about 3 min. In dried antennae the pheromone acetate is merely hydrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Several hypotheses have been proposed for odorant inactivation, such as odour sequestration by OBPs, internalization by ORs and enzymatic degradation in inactive or poorly active form by ODEs. Despite their potential important function in the dynamic of signal recognition, and in contrast to the great number of OBPs and ORs known to date in insects, only a few insect ODE genes have been identified and functionally characterized (review in Vogt, 2005), although early studies in moths revealed various enzymatic activities toward pheromone molecules in the sensillum lymph (Vogt and Riddiford, 1981;Kasang et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Several hypotheses have been proposed for odorant inactivation, such as odour sequestration by OBPs, internalization by ORs and enzymatic degradation in inactive or poorly active form by ODEs. Despite their potential important function in the dynamic of signal recognition, and in contrast to the great number of OBPs and ORs known to date in insects, only a few insect ODE genes have been identified and functionally characterized (review in Vogt, 2005), although early studies in moths revealed various enzymatic activities toward pheromone molecules in the sensillum lymph (Vogt and Riddiford, 1981;Kasang et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the estimation that in the presence of an antennae-specific pheromonedegrading enzyme (PDE) (6) the pheromone has a half-life of 15 ms, it has been suggested that pheromone signals are deactivated by an enzymatic process (7). On the other hand, the enzymatic degradation has been considered too slow (on a scale of minutes) when tested in intact antennae (8). Furthermore, it has been suggested that the discrepancy between the in vivo and in vitro experiments is due to the involvement of pheromone-binding proteins that protect the pheromone from degradation (9).…”
mentioning
confidence: 99%
“…Later, the turnover slowed down more than 100-fold, showing ca. 40% conversion after 30 min, and 75% conversion after 20 h. This time course differed from that seen in pheromone degradation, in antennae of B. mori (Kasang et al 1989a) and A. polyphemus (Kasang et al 1988), where the degradation proceeded more slowly, but continuously, and was almost complete after 30 min. The incomplete metabolism of benzoic acid might be due to higher antennal loads in the present study (1× 10 12 to 7× 10 13 molecules of benzoic acid per antenna) as compared with the pheromone loads (up to 5 ×10 11 molecules of bombykol per antenna).…”
Section: Discussionmentioning
confidence: 72%